Implementasi Penyelesaian Sengketa E-Commerce Dalam Hal Terjadinya Pelanggaran Pelaku Usaha - Putra, Audi Febriwidhia Aulia; Dianta, Dedon (Officium Notarium, 2025)
E-commerce is a platform that accommodates people's transaction needs using digital methods. The convenience offered by e-commerce not only has positive values, but also has negative impacts, with many people becoming victims of e-commerce crimes. This research aims to examine the regulations that legally protect consumers against all forms of e-commerce crime and examine how these laws are implemented in efforts to resolve consumer disputes. This normative legal research found that legislating consumer protection alone is not enough to eliminate all possibilities of online crime; consumers also need to be educated to prevent losses due to online crime or consumer negligence.